Contraction of polymer gels created by the activity of molecular motors. Issue 22 (29th May 2019) - Bacca, Mattia; Saleh, Omar A.; McMeeking, Robert M.
Abstract : We propose a theory based on non-equilibrium thermodynamics to describe the mechanical behavior of an active polymer gel created by the inclusion of molecular motors in its solvent. Abstract : We propose a theory based on non-equilibrium thermodynamics to describe the mechanical behavior of an active polymer gel created by the inclusion of molecular motors in its solvent. When activated, these motors attach to the chains of the polymer network and shorten them creating a global contraction of the gel, which mimics the active behavior of a cytoskeleton. The power generated by these motors is obtained by an ATP hydrolysis reaction, which transduces chemical energy into mechanical work. The latter is described by an increment of strain energy in the gel due to an increased stiffness. This effect is described with an increment of the cross-link density in the polymer network, which reduces its entropy. The theory then considers polymer network swelling and species diffusion to describe the transient passive behavior of the gel. We finally formulate the problem of uniaxial contraction of a slab of gel and compare the results with experiments, showing good agreement.